Ionization state of the accretion disc in the neutron star low-mass X-ray binary 4U 1728–34. Issue 3 (25th January 2019) - Lyu, Ming; Méndez, Mariano; Zhang, Jian-Fu; Xiang, Fu-Yuan
ABSTRACT: We analysed an XMM–Newton plus a simultaneous Rossi X-ray Timing Explorer observation and a separate Suzaku observation of the neutron star low-mass X-ray binary 4U 1728–34. We fitted the X-ray spectra with the self-consistent reflection modelrelxill . We found that the inclination angle of 4U 1728–34 is 49 ± 5 degree, consistent with the upper limit of 60 degree deduced from the absence of eclipses or dips in this source. The inclination angle in the fit of the XMM–Newton /RXTE observation is larger than 85 degree, which may be due to the possible calibration issues of the PN instrument in timing mode. We also found that the thermal emission from the accretion disc is not significant. This could be explained either by the relatively high column density of the interstellar medium along the line of sight to the source, which decreases the number of soft disc photons, or if most of the soft thermal photons from the disc are reprocessed in the corona. The ionization parameter derived from the fits is larger than the value predicted in the framework of the standard reflection model, wherein the disc is irradiated by an X-ray source above the compact object. This inconsistency suggests that irradiation from the neutron star and its boundary layer may play an important role in the ionization of the accretion disc, and hence in the reflection component in this source.